Analisa Perubahan Garis Pantai Di Kabupaten Indramayu Menggunakan NDWI - Alya Sekar Hapsari; Aning Haryati (Jurnal Perikanan Unram, 2024)
Indramayu Regency is one of the areas on the north coast of Java Island with a coastline length of ± 140 km. Over the past 15 years, abrasion and accretion phenomena have occurred in Indramayu Regency, causing significant changes to the coastline. Therefore, remote sensing technology is one of the solutions to identify beaches that experience shoreline changes. The purpose of the study was to analyze changes in coastline and determine the extent of accretion and abrasion in each sub-district in Indramayu Regency over time. The method used is Normalized Difference Water Index (NDWI) which identifies shoreline changes based on differences in water and land and detects changes in coastal accretion and abrasion. The data used is secondary data consisting of Landsat 8 OLI (Operational Land Imager) images in 2015, 2019, and 2023 and Indramayu Regency coastline data in 2015 sourced from Bappeda Indramayu Regency. The results of the analysis of the length of the coastline in Indramayu Regency have experienced significant changes where the coastline is getting longer. The difference in the length of the coastline is around ±3.29 km in the 2015-2019 period and around ±7.29 km in the 2015-2023 period. The results of the analysis show that there are significant changes in the incidence of accretion and abrasion in Indramayu Regency. In 2015 to 2023 the incidence of abrasion decreased by ± 49.51 Ha by about 20% and the incidence of accretion in 2015 to 2023 decreased by ± 93.88 Ha by about 25%.